Making headway with genetic diagnostics of intellectual disabilities. (26th August 2013) - Willemsen, M.H.; Kleefstra, T.
Abstract Until recently, the cause of intellectual disability (ID) remained unexplained in at least 50% of affected individuals. Recent advances in genetic technologies led to great new opportunities to elucidate genetic defects implicated in ID. The introduction of genome‐wide technologies that are able to detect small chromosomal copy number variations led to the identification of several microdeletion/duplication syndromes and to the subsequent identification of single causative genes. By the recent implementation of whole exome sequencing (WES) in research and diagnostics, with the potential to identify disease causing variants throughout the human exome at the base‐pair level, a new revolution has started. Several studies showed that WES is effective in the identification of ID genes. Here we provide an historical overview of the advances in diagnostics of ID and illustrate the high diagnostic potential of current technologies by presenting the diagnostic survey that we performed in a series of 253 individuals with previously unexplained ID. This is the first study that systematically evaluated the diagnostic yield of the currently available and rapidly developing genetic diagnostic arsenal. The results of our study indicate that application of present‐day genetic diagnostic technologies lead to a significant increase in the number of patients that can be diagnosed.